Electrocardiogram biometric system: Analytical Review - Khazaal, Tiba; Abbas, Thekra (Journal of Madenat Alelem University College, 2023)
Biometric features have recently been used for security, which has led to their widespread use. However, they can be threatened, faked, lost, or hacked. Recently, the ECG has been employed as a biometric tool, and it may be better suited because it contains precise, private, and secret information about the patient. The person’s identity was safeguarded and protected, and the ECG was utilized to identify him and prevent information violations. ECG identification has a lot of benefits and high accuracy, but it can also be affected by interference and noise in the ECG signals. This paper presents a few typical electrocardiogram measurement techniques and provides a comprehensive overview of electrocardiograms.